Political Regimes, Party Ideological Homogeneity and Polarization - Micael Castanheira; Benoit S Y Crutzen (Tinbergen Institute, 2022)
We develop a model of elections in which parties choose their ideological position and the ideology of their candidates. Tighter candidate selection reduces policy uncertainty for voters. We show that weak institutional constraints, as in a Presidential regime, induce parties to allow their candidates to be ideologically heterogeneous. Tighter constraints or reduced voter polarization induces them to choose an ideologically homogeneous set of candidates. This highlights a multiplier effect of intraparty candidate selection: the parties' best responses amplify institutional and socio-economic changes. These effects rationalize why mainstream parties look so different across the two sides of the Atlantic. Around the middle of the nineteenth century, when facing similar organizational challenges, parties made opposite choices that still apply to this day: the introduction of direct primaries in the US, which decentralized candidate selection, versus the tightening and centralization of selection in Victorian England.
Keywords: 330; parties as brands; political regime; intraparty candidate selection; ideology; polarization